Multi-omics dissection of tumor microenvironment-mediated drug resistance: mechanisms and therapeutic reprogramming - Chen, Fanghua; Fu, Yuandong; Bai, Gaigai; Qiu, Junjun; Hua, Keqin (Frontiers in Pharmacology, 2025)
Tumor drug resistance represents a major challenge in contemporary cancer therapeutics, significantly compromising the clinical efficacy of chemotherapy, targeted therapy, and immunotherapy. While existing research has elucidated the critical role of tumor cell-intrinsic mechanisms in drug resistance—including genomic instability, persistent activation of signaling pathways and aberrant epigenetic modifications—emerging evidence highlights the crucial involvement of dynamic remodeling within the tumor microenvironment (TME) in driving therapeutic resistance. The TME fosters drug resistance through dynamic remodeling, creating hypoxic conditions, immunosuppressive networks, and metabolic stress, which collectively impair treatment response and promote therapeutic escape. Advances in multi-omics technologies now enable a comprehensive, multi-dimensional analysis of these interactions, integrating genomic, epigenomic, transcriptomic, proteomic, and metabolomic data to uncover critical molecular networks and vulnerabilities. In this review, we explore the key mechanisms by which the TME influences drug resistance, discuss how multi-omics approaches enhance our understanding of these processes and evaluate emerging therapeutic strategies aimed at reprogramming the TME to overcome resistance.